Berl: the biography of a socialist Zionist : Berl Katznelson, 1887-1944 - Shapira, Aniṭah (Cambridge University Press, 1984)
Anita Shapira: "Berl". The Biography of a Socialist Zionist. Berl Katznelson 1887 to 1944. Cambridge University Press, Cambridge-London-New York-Rochelle-Melbourne-Sydney 1984, 400 Seiten, 17,50 Pfund Sterling